2010
DOI: 10.1002/app.31869
|View full text |Cite
|
Sign up to set email alerts
|

Chelation ion‐exchange study of copolymer resin derived from 8‐hydroxyquinoline 5‐sulphonic acid, oxamide, and formaldehyde

Abstract: Copolymers (8-HQ5-SAOF) were synthesized by the condensation of 8-hydroxyquinoline 5-sulphonic acid (8-HQ5-SA) and oxamide (O) with formaldehyde (F) in the presence of acid catalyst. Four different copolymers were synthesized by using varied molar proportion of the reacting monomers. Copolymer resin composition has been determined on the basis of their elemental analysis and average molecular weights of these resins were determined by conductometric titration in nonaqueous medium. Viscometric measurement in di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
10
0
1

Year Published

2010
2010
2017
2017

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 14 publications
(11 citation statements)
references
References 15 publications
0
10
0
1
Order By: Relevance
“…It should be mentioned that a weak broad peak at approximately 3280 cm -1 was also revealed in each spectrum, which might have been attributed to the formation of intermolecular hydrogen bonding between the functional groups of the pre-polymers, including CH2OH, NH, and NH2, and the by-products of the condensation reaction, such as water and free formaldehyde (Zorba et al 2008;Singru and Gurnule 2010;Šmidriaková and Laurová 2011). This band was remarkably stronger in the spectrum of the Latin Walnut paper than that in the spectrum of the Walnut paper, which indicated that noticeably higher contents of water and reactive groups for hydrogen bonding existed in the Latin Walnut-saturated paper surface.…”
Section: Fig 5 Atr Ft-ir Spectra Obtained From the Uf-saturated Latmentioning
confidence: 98%
“…It should be mentioned that a weak broad peak at approximately 3280 cm -1 was also revealed in each spectrum, which might have been attributed to the formation of intermolecular hydrogen bonding between the functional groups of the pre-polymers, including CH2OH, NH, and NH2, and the by-products of the condensation reaction, such as water and free formaldehyde (Zorba et al 2008;Singru and Gurnule 2010;Šmidriaková and Laurová 2011). This band was remarkably stronger in the spectrum of the Latin Walnut paper than that in the spectrum of the Walnut paper, which indicated that noticeably higher contents of water and reactive groups for hydrogen bonding existed in the Latin Walnut-saturated paper surface.…”
Section: Fig 5 Atr Ft-ir Spectra Obtained From the Uf-saturated Latmentioning
confidence: 98%
“…[32,34,35] Finally, the reported resin is found to be a very effective hazardous metal ion-exchanger than the earlier reported resins. [5,12,18,35] CONCLUSION A novel chelating resin was synthesized for the recovery of harmful metal ions. The synthesized resin was characterized by various spectral techniques, and its morphological features were analyzed.…”
Section: Freundlich Isotherm Modelmentioning
confidence: 99%
“…Batch equilibrium method was adapted to determine the efficiency of the metal ion uptake capacity of the terpolymer resin under different experimental conditions according to earlier literatures. [16][17][18] Desorption and regeneration studies Exactly, 25 mg of ANAF terpolymer resin was added to 25 ml of 0.1 M metal ion solution in Erlenmeyer flask and mechanically shaked for 1 h. After the shaking time, the resin was filtered off and washed several times with distilled water to remove the excess of metal ion. Then, the resin was treated with 25 ml of 0.01 M NaOH solution in Erlenmeyer flask at the conditions discussed above.…”
Section: Batch Separation Analysismentioning
confidence: 99%
See 1 more Smart Citation
“…The batch equilibrium method was employed to remove the selective metal ions. The copolymer reported a good metal ion uptake for Fe(III), Cu(II) and Ni(II) ions than for Co(II), Zn(II), Cd(II) and Pb(II) ions [2].…”
Section: Introductionmentioning
confidence: 99%